The relationship between human resource management practices and employee attitudes: a case of Tobacco Research Board - Goneso, Ethel (Midlands State University, 2019)
The study examined the relationship between Human Resource Management Practices and employee attitudes among employees at Tobacco Research Board. 210 participants took part in the study which comprised of 120 males and 90 females and stratified random sampling. Participants’ age ranged from 23 – 59 years. Participants also had different levels of education and different working years in the organization. Correlation coefficient indicated that there was a high positive relationship between Human Resource Management Practices and employee attitudes which can therefore be credited that employees who engage in HRM practices produce positive attitudes for instance training and development brings in job involvement and practices like compensation and benefits are reciprocated by employees through job satisfaction. A quantitative research approach that employ descriptive survey was adopted in this paper to describe current situations and conditions. Data was collected using a set of questionnaires and it was analysed through the use of SPSS Version 16. Recommendations for future researchers, managers and employees were done in the study.